(untitled) (Journal of Intellectual Property and Information Technology Law (JIPIT), 2021)
The Centre for Intellectual Property and Information Technology Law (CIPIT) has been studying the impact of digital identities on society. This has included policy research on the legal and technical aspects of the national digital ID system Huduma Namba under which the Government is integrating all its identification documents. This research shows that the national digital identity system also integrates with privately issued digital identities such as mobile phone numbers and social media accounts. We anticipate that as national digital ID uses increase, so will the linkage with private systems. This is already evident from e-government services, where payments for Government services, such as passport applications, drivers’ licences, national health insurance and hospital bills in public hospitals are made using mobile money platforms. We also appreciate that private digital ID is more developed and has more uses than national digital ID. For example, a 2019 survey, undertaken by the Central Bank of Kenya (CBK), estimates that access to financial products had risen from 26.7% in 2006 to 89% of the population in 2019. This is attributed partly to the availability of digital products such as “mobile banking, agency banking, digital finance and mobile apps”. These products make use of personal data, which broadly falls under digital identities. This study seeks to understand the privacy implications of digital ID by looking at digital lending apps.